Co-Occurring Non-Suicidal Self-Injury and Firesetting Among At-Risk Adolescents: Experiences of Negative Life Events, Mental Health Problems, Substance Use, and Suicidality. - Tanner, A.; Hasking, Penelope; Martin, G. (2016)
Co-occurring internalizing and externalizing problem behaviors in adolescence typically marks more severe psychopathology and poorer psychosocial functioning than engagement in a single problem behavior. We examined the negative life events, emotional and behavioral problems, substance use, and suicidality of school-based adolescents reporting both non-suicidal self-injury (NSSI) and repetitive firesetting, compared to those engaging in either behavior alone. Differences in NSSI characteristics among self-injurers who set fires, compared to those who did not, were also assessed. A total of 384 at-risk adolescents aged 12-18 years (58.8% female) completed self-report questionnaires measuring NSSI, firesetting, and key variables of interest. Results suggest that adolescents who both self-injure and deliberately set fires represent a low-prevalence but distinct high-risk subgroup, characterized by increased rates of interpersonal difficulties, mental health problems and substance use, more severe self-injury, and suicidal behavior. Implications for prevention and early intervention initiatives are discussed.